The decision by Western Kentucky University to transition to NCAA Division I athletics and the Football Bowl Subdivision - Spencer, Tyler C.; Hambrick, Marion E. (London : SAGE Publications: SAGE Business Cases Originals, 2019)
Colleges and universities competing in National Collegiate Athletic Association (NCAA) Division I (DI) athletics in the Football Bowl Subdivision (FBS) have received greater exposure, financial gains, and other benefits compared with institutions competing in lower divisions. Since 1978, 28 schools have transitioned to the FBS. In 2006, Western Kentucky University (WKU) administrators voted to join these schools and make the transition. The NCAA approved the request three years later in 2009. The transition had the potential to generate both positive and negative consequences for the athletic department and university. These included changes in ticket sales, marketing, and fundraising for the athletic department and changes in student admissions, enrollment, and retention, as well as fundraising and marketing for the university. This case asks readers to take a retrospective look at WKU, evaluating the effects of the DI/FBS transition after its first ten years. Readers have an opportunity to assess the on-field and off-field outcomes of this decision.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; National Collegiate Athletic Association -- Case studies; Athletics -- Kentucky -- Case studies; College sports -- Kentucky -- Case studies; Football -- Kentucky -- History -- 21st century -- Case studies